Epidemiology, clinical features and management of autoimmune hepatitis in Switzerland: a retrospective and prospective cohort study (Swiss Medical Weekly, 2023)
BACKGROUND AND AIMS: The Swiss Autoimmune Hepatitis Cohort Study is a nationwide registry, initiated in 2017, that collects retrospective and prospective clinical data and biological samples from patients of all ages with autoimmune hepatitis treated at Swiss hepatology centres. Here, we report the analysis of the first 5 years of registry data.RESULTS: A total of 291 patients with autoimmune hepatitis have been enrolled, 30 of whom were diagnosed before 18 years of age and composed the paediatric cohort. Paediatric cohort: median age at diagnosis 12.5 years (range 1–17, interquartile range (IQR) 8–15), 16 (53%) girls, 6 (32%) with type 2 autoimmune hepatitis, 8 (27%) with autoimmune sclerosing cholangitis, 1 with primary biliary cholangitis variant syndrome, 4 (15%) with inflammatory bowel disease and 10 (41%) with advanced liver fibrosis at diagnosis. Adult cohort: median age at diagnosis 54 years (range 42–64, IQR 18–81), 185 (71%) women, 51 (20%) with primary biliary cholangitis variant syndrome, 22 (8%) with primary sclerosing cholangitis variant syndrome, 9 (4%) with inflammatory bowel disease and 66 (32%) with advanced liver fibrosis at diagnosis. The median follow-up time for the entire cohort was 5.2 years (IQR 3–9.3 years). Treatment in children: 29 (97%) children were initially treated with corticosteroids, 28 of whom received combination treatment with azathioprine. Budesonide was used in four children, all in combination with azathioprine. Mycophenolate mofetil was used in five children, all of whom had previously received corticosteroids and thiopurine. Treatment in adults (data available for 228 patients): 219 (96%) were treated with corticosteroids, mostly in combination with azathioprine. Predniso(lo)ne was the corticosteroid used in three-quarters of patients; the other patients received budesonide. A total of 78 (33%) patients received mycophenolate mofetil, 62 of whom had previously been treated with azathioprine. Complete biochemical response was achieved in 13 of 19 (68%) children and 137 of 182 (75%) adults with available follow-up data. All children were alive at the last follow-up, and none had undergone liver transplantation. Five (2%) adults underwent liver transplantation, two of whom had a fulminant presentation. Four (2%) adults with autoimmune hepatitis died (two from liver-associated causes).CONCLUSION: Patients with autoimmune hepatitis in Switzerland had clinical features similar to those in other cohorts. The proportion of patients diagnosed with primary biliary cholangitis variant syndrome was higher than expected. Autoimmune hepatitis was managed according to guidelines, except for the use of budesonide in a small proportion of paediatric patients. The outcomes were excellent, but the findings must be confirmed over a longer follow-up period.